A Collection of Orientalist Paintings in the Imperial Private Gallery in Naples - Polański, Tomasz (Anabasis. Studia Classica et Orientalia, 2011)
Pliny the Elder’s history of sculpture and painting can be read largely as a guide to the Roman art galleries of his time. Philostratus the Elder in his turn compiled a learned guide to a painting gallery in Naples (Imagines). I focus on a selection of ‘Orientalist’ paintings from Philostratus the Elder’s gallery (Heracles and Antaeus, Heracles and the Pygmies, The River Nile, Memnon, Pantheia, Rhodogoune). Philostratus the Elder confronted the Greek hero ‘short in stature but in soul unflinching’ with the Libyan savage whose body was ridiculously distorted, his limbs overgrown and unnaturally swollen which emphasised his primitivism. According to Philostratus’ description the artist counterpoised two contrasting forces: the young Greek’s skill and power against the brutal force of primitivism. This image of the non-Greek neighbouring peoples had already been deeply rooted in the Greek mentality for a long time in fact. Heracles and the Pygmies’ painting was conspicuous for its air of grotesque, parody and burlesque. The Graeco-Roman attraction with Africa was a mixture of fascination, fear and alienation. Rhodogoune’s story reflected the popular archetype of Oriental warrior-queen, both brave and beautiful, vengeful, cruel and cunning. The painting of Rhodogoune was remarkable for its specific mixture of Hellenic components (facial portrait, composition, illusionist forms) and Oriental elements (textiles, harness, weaponry, fashion of dress) combined together. The predominantly Classical subjects and exclusively Classical form of the paintings from the Neapolitan gallery well portrays the cultural milieu of the Severan court, hellenized Rome with an Oriental undercurrent. This strange blend of Hellenic and Oriental ingredients is also symptomatic of the Parthian art. The collection of paintings complied with the artistic tastes, intellectual occupations and Arabian origin of the Empress Julia Domna, who was probably the owner of that refined and precious art gallery at Naples.